A dispersion model of an open microstrip-line using the LSM propagation mode - Galo Durango, Augusto (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The study of one of the propagation modes, in the range of the microwave frequencies, of a transmission line conformed by two conductor planes, which is well known in the pertinent literature as an open or a “microstrip-line” is shown in this work. Open in the sense of that one of the conductors is exposed to the vacuum. That is, this device is basically conformed, if we have in account the thin film technology, of two conductive parallel planes and two dielectrics ones and this has been developed of the classical transmission line for low frequencies. The upper conductor plane has finite transversal dimensions with respect to the lower one. In the field of the Complex Variable Theory it is possible to study the LSM propagation mode in a P transformed plane, which was obtained from the physical plane (Z semiplane) of the microstrip-line through two consecutive Schwarz-Christoffel transformations. It is also possible to find the phase constant T, the Electric and Magnetic fields and finally the equations for the LSM mode. Once this information is obtained, graphics will be made for the effective dielectric constant of the means as a function of the angular frequency and the W/h profile relation of the device. Finally, comparisons will be made with the results offered by others authors.